Assessement of genotoxicity of Dichlorvos to Mystus vittatus (Bloch) by comet assay - Devesh, Shukla; Nagpure, N S; Ravindra, Kumar; Poonam J, Singh (Indian Journal of Fisheries, 2016)
In the present study, the genotoxicity of dichlorvos, a widely used organophosphate pesticide, was assessed in the air-breathing teleost fish Mystus vittatus using comet assay. The specimens were exposed to sublethal concentrations of pesticide, viz., 0.045 and 0.022 ppm for a period of one week and the blood samples were collected at 24 h intervals for assessment of DNA damage in terms of Olive tail moment in the erythrocytes. Significant (p<0.01) effects of both concentration and time of exposure on DNA damage were observed in the exposed fish. The lowest DNA damage was observed on day 1 at sublethal 1 concentration, followed by gradual increase in DNA damage with increase in concentration and duration of exposure. The study, thus, revealed the potential hazard of the pesticide to fishes and also indicated suitability of the comet assay to detect DNA damage induced by the pesticide even at lower concentrations.